2023
DOI: 10.1038/s41598-023-35587-6
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-lipoic acid attenuates heat stress-induced apoptosis via upregulating the heat shock response in porcine parthenotes

Abstract: Heat stress (HS) is a long-standing hurdle that animals face in the living environment. Alpha-lipoic acid (ALA) is a strong antioxidant synthesized by plants and animals. The present study evaluated the mechanism of ALA action in HS-induced early porcine parthenotes development. Parthenogenetically activated porcine oocytes were divided into three groups: control, high temperature (HT) (42 °C for 10 h), and HT + ALA (with 10 µM ALA). The results show that HT treatment significantly reduced the blastocyst forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Alpha-lipoic acid (ALA) has emerged as a potent antioxidant that scavenges ROS and provides reduced GSH, thus inhibiting the formation of free radicals to maintain cellular redox homeostasis. Recent research has demonstrated ALA’s ability to prevent heat-induced apoptosis in porcine oocytes by regulating heat shock factors (HSFs) and mitigating oxidative and endoplasmic reticulum stresses [ 208 ]. In addition, it was found that ALA significantly upregulated the level of Bcl-2 and glutathione (GSH) and reduced the expression of caspase 3.…”
Section: Role Of Exogenous Antioxidant Supplementation In Relieving H...mentioning
confidence: 99%
“…Alpha-lipoic acid (ALA) has emerged as a potent antioxidant that scavenges ROS and provides reduced GSH, thus inhibiting the formation of free radicals to maintain cellular redox homeostasis. Recent research has demonstrated ALA’s ability to prevent heat-induced apoptosis in porcine oocytes by regulating heat shock factors (HSFs) and mitigating oxidative and endoplasmic reticulum stresses [ 208 ]. In addition, it was found that ALA significantly upregulated the level of Bcl-2 and glutathione (GSH) and reduced the expression of caspase 3.…”
Section: Role Of Exogenous Antioxidant Supplementation In Relieving H...mentioning
confidence: 99%